Analysis of Raw Material Inventory Planning to Minimise Stock Out and Stock Out Cost Using Min-Max and Eoq Methods at PT XYZ - Fauziah, Salsabila Nurul; Hati, Shinta Wahyu (Politeknik Negeri Batam, 2024)
PT XYZ is a manufacturing company that produces and sells wire harnesses for automotive vehicles and related components. There are various types of raw materials in wire harness assembly. Therefore, raw material control planning is important to avoid stock outs and waste of costs. This quantitative descriptive research aims to determine the minimum and maximum inventory limits so that stock outs do not occur, as well as determine the optimum number of orders and the amount of costs that can be saved so that there is no waste of costs. The data analysis techniques used are first, min-max analysis by calculating the minimum and maximum inventory, safety stock and reorder point. Second, EOQ analysis by knowing the annual demand or need for raw materials, the amount of ordering costs and storage costs. The results of the calculation with min-max obtained minimum stock limits (reorder point) terminal A, terminal B and wire A respectively 913 m, 702 m and 1,104 m, maximum limits 1,826 m, 1,405 m and 2,208 m. Based on EOQ calculations, the optimum values are 4,055 m, 2,287 m and 3,911 m. These results can help save costs for each material by 41%, 2% and 6%.